Analysis of indicators of activity of children's dental service in the Poltava region (2014–2016) - N. O. Lyakhova (Сучасні медичні технології, 2020)
Purpose of the study. Analysis of qualitative and quantitative indicators of activity of institutions providing dental care for children of Poltava region for 2014–2016.